1978
DOI: 10.1148/129.3.653
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Osteonecrosis of the Knee and Medial Meniscal Tears

Abstract: Several factors may play a role in the etiology of "spontaneous" osteonecrosis of the medial femoral condyle. Corticosteroids are known to induce osteonecrosis, and 45% of the patients in this study received steroids parenterally or by intra-articular injection. Another factor, heretofore given little attention, is the association of medial meniscal tears and "spontaneous" osteonecrosis. Twenty-one (78%) of 27 knees examined by arthrography demonstrated meniscal tears. Stress concentration over the edge of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

1980
1980
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(34 citation statements)
references
References 0 publications
0
32
0
2
Order By: Relevance
“…All four patients presented knee osteoarthritic changes, showed medial meniscus tear on MR imaging, and three of them were osteopenic. Several authors have suggested that the presence of medial meniscus tears, osteoarthritis, and/or osteoporosis may be a significant contributing factor in the development of subchondral plate microfractures [4,10,15,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All four patients presented knee osteoarthritic changes, showed medial meniscus tear on MR imaging, and three of them were osteopenic. Several authors have suggested that the presence of medial meniscus tears, osteoarthritis, and/or osteoporosis may be a significant contributing factor in the development of subchondral plate microfractures [4,10,15,17].…”
Section: Discussionmentioning
confidence: 99%
“…The diminished load-bearing capacity of injured meniscus increases the applied forces to the subchondral plate [14,17]. In the same way, osteoporosis and cartilage thinning seen on osteoarthritis can weaken the loadbearing capacity of subchondral bone, such that stress fracture can result from normal activity [4,9].…”
Section: Discussionmentioning
confidence: 99%
“…This pain is so sudden that the patient frequently remembers the exact moment or activity during which the symptoms started. This pain is initially severe, and remains present at rest [31,33,41,42]. The pace of disease progression depends on its location and size.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…A mechanical or microtraumatic origin has progressively emerged as the most likely underlying mechanism of SONK [4,33,41,52]. According to this hypothesis, repetitive impact or stress on the epiphyseal bone plate and underlying trabecular network may induce microfractures in the trabecular bone, especially if this bone is weakened by osteopenia [16,41,42,45,46,49,55,56]. Accumulation of these microfractures with failure of repair mechanisms could induce subchondral bone destruction, which may eventually lead to subchondral bone plate collapse typical for epiphyseal osteonecrosis.…”
Section: Pathogenesismentioning
confidence: 99%
“…The theories include vascular insufficiency or microfractures of the subchondral plate, with deviation of the synovial fluid from the synovial space to inside the bone. An association between meniscal lesions and osteonecrosis has also been postulated (2,3) . Idiopathic osteonecrosis can also be named avascular necrosis, aseptic necrosis, spontaneous osteonecrosis or Ahlbäck's disease.…”
Section: Introductionmentioning
confidence: 98%